PERAN CORPORATE GOVERNANCE DALAM MENURUNKAN KEBANGKRUTAN PADA PERUSAHAAN DI INDONESIA - Hilaliya, Tasya; Margaretha, Farah (Jurnal Akuntansi, 2017)
This research examines the influence of Corporate Governance on Firm Performance measured by Tobin's Q and Financial Distress measured by Z-score. The samples used were 72 companies engaged in the manufacturing industry are listed on the Indonesia Stock Exchange (BEI) for five years from 2011 to 2015. The analytical methods used in this research is panel data regression, discriminant analysis, and logistic regression. The results showed that (I) there is no significant impact between corporate governance practices on firm performance. (2) there is negative impact between corporate governance practices on financial distress. Then, the companies need to increase corporate governance in order to avoid possibility of financial distress and for the investor before making an investment should consider the factors that affect the firm performance and financial distress